Горшкоподібний посуд: етнокультурні взаємовпливи - Мотиль, Р. (Інститут народознавства НАН України, 2008)
The article brings complex comparative analitical study in Ukrainian and foreign types of pottery kitchenware with throwing light upon common and different features in forms and decorations of artefacts as well as with definitions of most characteristic notions that underline originality and nature of Ukrainian ceramics in the context of All-European culture.